TRISPECIFIC BROADLY NEUTRALIZING ANTIBODIES, N6/PGDM1400-10E8V4 DELIVERED BY RECOMBINANT ADENO-ASSOCIATED VIRUS (RAAV8) VECTOR: A NOVEL VACCINE FOR HIV/AIDS INFECTION - Mangkuliguna, Ghea; Glenardi, Glenardi (Essential: Essence of Scientific Medical Journal; Vol 17 No 1 (2019): Volume 17 No. 1 (Januari-Juni 2019) ESSENTIAL: Essence Of Scientific Medical Journal, 2019)
ABSTRACT   Introduction: Developing a human immunodeficiency virus (HIV) vaccine with excellent efficacy has become a global urgency that must be addressed immediately. However, the highly diversified HIV-1 envelope glycoprotein (Env) proved to be a challenge in generating an effective HIV vaccine and therapy. HIV/AIDS has already become one of the world's major health issues taking its toll on millions of lives each year. Broadly neutralizing antibodies (bnAbs) as the latest therapy shows excellent promise as a novel vaccine to fight the HIV epidemic. Nevertheless, bNAb as an individual therapeutic agent is not potent enough to fight against the diversity of the HIV epitope. Recently, trispecific N6/PGDM1400-10E8v4, a combination of three various bNAbs has been developed and it has been proven to be the most potent therapy developed at present. Discussion: This literature review yield results that trispecific N6/PGDM1400-10E8v4 was able to neutralize a large margin of 208 HIV-1 strains up to 99% at IC 50 <1.0 ?g/ml by targeting multiple epitopes at the same time without losing each of its parental antibodies affinity. We particularly highlight the use of rAAV8 to deliver the bNAbs in order to ensure long-term expression and secretion of antibodies in those infected with HIV. Conclusion: Thus, the potent and breadth neutralizing ability of trispecific N6/PGDM1400-10E8v4, making it an excellent candidate to become the future HIV vaccine.   Keyword: broadly neutralizing antibodies, HIV, rAAV8, trispecific N6/PGDM1400-10E8v4